Clinical study of long-term treatment using erythromycin in chronic lower respiratory tract infection - Konishi, Mitsuru; Sawaki, Masayoshi; Mikasa, Keiichi; Maeda, Koichi; Narita, Nobuhiro (Japanese Journal of Chemotherapy, 1998)
In order to establish useful therapeutic methods in chronic lower respiratory tract infection, we carried out long-term tratment (12-41 months) of erythrymycin (EM) using dosages of 600-1, 200 mg/day. Thirteen cases with diffuse panbronchiolitis (DPB) were the subjects of this study. All patients complained of large amounts of purulent sputum and DOE, and had decreasing of PO2 levels. Major infections of Haemophilus influenzae and Pseudomonas aeruginosa bacteria were detected by TTA before EM therapy. The clinical responses to treatment were markedly effective (1 case) effective (10 cases) and mildly effective (2 cases). Two cases infected by P. aeruginosa had effective responses to treatment. Improvement of QOL was noted in all cases, and no significant side effects were noted during the long-term treatment. Early intervention with EM treatment was required because the clinical responses were considered less efffective in cases with elevated PCO2. The causative bacteria of acute exacerbation during EM treatment were mainly H. influenzae or Streptococcus pneumoniae, which easily developed after viral infections of P. aeruginosa or in cases which bacteria can not be detected significant amounts from sputum. In erythromycin- ineffective patients, long-term clarithromycin treatment was found effective. EM therapy for DPB may be discontinued, when the clinical manifestations of disease (especially purulent sputum) disappear, and the diffuse, nodular opacities in chest roentgenogram almost completely resolve. We consider these results indicate that this therapy is a new and useful treatment for chronic lower respiratory tract infections.